Plasma and aqueous levels of subfatin, preptin and betatrophin in patients with diabetic retinopathy - Kobat, Sabiha Gungor; Gul, Fatih Cem; Celik, Fatih; Uzun, Seda Liman; Kobat, Mehmet Ali; Akkoc, Ramazan Fazil; Aydin, Suleyman (Bmc, 2023)
AimTo examine subfatin, preptin and betatrophin levels in plasma and aqueous in patients with diabetes mellitus (DM) (with and without retinopathy).Material and methodSixty patients, who were similar in terms of age and gender, and were scheduled for operation due to cataract, were included in the study. The patients were divided into three groups as Group C (20 weeks without diabetes and comorbidity), Group DM (20 patients with DM but no retinopathy) and Group DR (20 patients with diabetic retinopathy). The preoperative body mass index (BMI), fasting plasma glucose, HbA1c, lipid profile levels of all patients in the groups were examined. Blood samples were also taken for plasma subfatin, preptin and betatrophin levels. At the beginning of the cataract surgery, 0.1 ml of aqueous fluid was taken from the anterior chamber. Plasma and aqueous subfatin, preptin and betatrophin levels were analyzed by ELISA (enzyme-linked immunosorbent assays) method.ResultsIn our study results, there was a significant difference in BMI, fasting plasma glucose and hemoglobin A1c levels (p < 0.05 for all parameters). Plasma and aqueous subfatin levels were higher in Group DR compared to Group C (p < 0.001, p = 0.036, respectively). Plasma and aqueous preptin levels were higher in group DR and group DM than in group C (p = 0.001, p = 0.002, p < 0.001, p = 0.001, respectively). Plasma and aqueous betatrophin levels were higher in Group DR compared to group C (p = 0.001, p = 0.010, respectively).ConclusionSubfatin, preptin and betatrophin molecules may have an important role in the pathogenesis of diabetic retinopathy.
Keywords: Diabetes mellitus; Retinopathy; Subfatin; Preptin; Betatrophin